Bioactive camel milk peptides as regulators of insulin receptor signaling: Experimental and computational perspectives - Issoufou Katambe Mohamed; Yufei Hua; Xiangzhen Kong; Xingfei Li; Yeming Chen; Caimeng Zhang; Mouhamed Fall (Results in Chemistry)
Insulin resistance (IR), a hallmark of type 2 diabetes mellitus (T2DM), disrupts insulin receptor (IR) activation and downstream signaling, leading to impaired glucose homeostasis. Bioactive peptides have emerged as promising modulators of IR function; however, their mechanisms of action remain largely elusive. This study investigates the molecular effects of four camel milk-derived peptides on IR activation using an integrative approach combining cell-based assays and structure-based computational analysis.Among the peptides, TYYPPQ exhibited the most potent biological activity in insulin-resistant HepG2 cells, significantly restoring IR expression at both mRNA and protein levels and robustly reactivating AKT phosphorylation. Molecular docking, molecular dynamics simulations, and in silico mutagenesis revealed that TYYPPQ binds allosterically to the inactive IR kinase domain, engaging key regulatory residues Glu1047 and Asp1150 within the DFG motif and activation loop. This interaction stabilizes the activation loop in an open conformation, reduces its flexibility, and facilitates autophosphorylation, thereby promoting receptor activation. Unlike previously studied peptides or ATP analogs that act competitively at the ATP-binding site, TYYPPQ exhibits a non-competitive, allosteric activation mechanism, characterized by persistent hydrogen bonding with Glu1047 and favorable hydrophobic interactions. MM/GBSA analysis confirmed strong binding affinity (ΔG = −81.89 kcal/mol), and in silico mutagenesis validated the critical anchoring role of Glu1047.These findings uncover a novel mechanism by which TYYPPQ allosterically activates IR, offering a distinctive strategy for restoring insulin sensitivity. Our combined biochemical and computational framework provides a foundation for rational design of next-generation peptide-based therapeutics targeting IR dysfunction in T2DM.